Target Cultures Representation in English Course Books of Smart 10 and Bahasa Inggris X for Senior High School - Dewi Musfika Santi; Bambang Widi Pratolo (Premise: Journal of English Education and Applied Linguistics, 2022)
This research is aimed to analyze the target cultural classification aspects of High School textbooks. The data for analysis were collected from two High School books entitled Smart 10 and Bahasa Inggris X. The method employed was the descriptive qualitative method, and it used the theory from Dweik & Al-Sayyed (2015) about cultural classifications. This study explored and compared how the target culture was represented in two coursebooks that used purposive sampling. Three available units were selected in every book by employing systemic random sampling. Six aspects were analyzed; food & beverages, person's name, places, social behavior, ecology, and economy. The results showed that target cultures represented by Smart 10 are more dominant than in Bahasa Inggris X's book.